Model For Measuring The Level Of OHS Maturity Based On The Level Of Job Satisfaction - Nasrulloh, Nasrulloh; Purnomo, Hari (JTI: Jurnal Teknik Industri, 2024)
In the current electricity development project, the understanding of OSH does not seem to be fully implemented. One indication that the knowledge of OSH has not been fully implemented is that workers are still unaware of the hazards associated with their work. Based on these issues, the question is whether intrinsic factors (motivation) and extrinsic factors (hygiene) influence job satisfaction and worker performance in achieving zero accidents. This research will focus on how the measurement model can influence the OHS maturity level and what design strategies will be used to improve the OHS maturity level performance. This research aims to obtain a measurement model that can influence the OHS Maturity Level and provide a design strategy used to improve the OHS Maturity Level. The author uses quantitative methods and collects data from 516 PT PLN (Persero) UIP Nusa Tenggara Working Partners correspondents. Data testing methods include the measurement model test, structural equation model test, model accuracy test (goodness of fit), and hypothesis test. The results showed that job satisfaction variables, directly and indirectly, affect K3 Maturity Level performance. Therefore, a programme design is needed to maintain the K3 Maturity Level performance results and increase the value of the current K3 Maturity Level performance results. Policy-based programmes and communication-based programmes are the programme designs. These two programs aim to maintain and improve the value of the OHS Maturity Level performance. Keywords:hygiene factors, motivational factors, job satisfaction, OHS maturity level performance